The role of Wnt signalling in development of coronary artery disease and its risk factors - Liu, Ya (Open Biol, 2020)
The Wnt signalling pathways are composed of a highly conserved cascade of events that govern cell differentiation, apoptosis and cell orientation. Three major and distinct Wnt signalling pathways have been characterized: the canonical Wnt pathway (or Wnt/β-catenin pathway), the non-canonical planar cell polarity pathway and the non-canonical Wnt/Ca(2+) pathway. Altered Wnt signalling pathway has been associated with diverse diseases such as disorders of bone density, different malignancies, cardiac malformations and heart failure. Coronary artery disease is the most common type of heart disease in the United States. Atherosclerosis is a multi-step pathological process, which starts with lipid deposition and endothelial cell dysfunction, triggering inflammatory reactions, followed by recruitment and aggregation of monocytes. Subsequently, monocytes differentiate into tissue-resident macrophages and transform into foam cells by the uptake of modified low-density lipoprotein. Meanwhile, further accumulations of lipids, infiltration and proliferation of vascular smooth muscle cells, and deposition of the extracellular matrix occur under the intima. An atheromatous plaque or hyperplasia of the intima and media is eventually formed, resulting in luminal narrowing and reduced blood flow to the myocardium, leading to chest pain, angina and even myocardial infarction. The Wnt pathway participates in all different stages of this process, from endothelial dysfunction to lipid deposit, and from initial inflammation to plaque formation. Here, we focus on the role of Wnt cascade in pathophysiological mechanisms that take part in coronary artery disease from both clinical and experimental perspectives.